Effect of Occupation and Smoking on Respiratory Symptoms in Working Children - ÖZEN, AHMET OĞUZHAN; KARADAĞ, BÜLENT TANER; AY, NADİYE PINAR (WILEY, 2009)
Objectives To compare the respiratory symptoms and the lung function of children who work in different occupational groups. Methods The study was performed among children attending vocational training centers. The participants were evaluated in six different occupation groups. Chronic cough, wheezing and shortness of breath were evaluated by questionnaire. The association of independent variables with the respiratory symptoms was investigated through both univariate and multivariate methods. Results Among 642 children, 534 were males: the mean age was 17.7 +/- 1.0 years. Using an internal reference group, the odds ratios of chronic cough were significantly higher in the lathe (OR: 2.0, 95%CI: 1.07-3.74), coiffure (OR: 1.94. 95%CI: 1.01-3.70), and electricity-construction (OR: 2.63, 95%CI: 1.06-6.54) groups after adjustment for smoking, age, gender, and work characteristics. There were no significant differences in spirometric values between occupational groups in either smoking or non-smoking males. In non-smoking females, median values of FEV1 (P: 0.046), PEF (P: 0.0005) and FEF25-75% (P: 0.019) were lower in the textile compared to the coiffure group. There was no significant association between the total working time and spirometric values. There was no statistically significant relationship between the work-related factors and the smoking status. Conclusions The prevalence of chronic cough was higher in the lathe, coiffure, and electricity-construction groups and pulmonary function tests were lower in the non-smoking textile female group. Working children should be screened for respiratory symptoms and disease. Am. J. Ind. Med. 52:471-478, 2009. (c) 2009 Wiley-Liss, Inc.
Keywords: child labor; occupation; respiratory; spirometry; smoking; OBSTRUCTIVE PULMONARY-DISEASE; LUNG-FUNCTION; CHRONIC-BRONCHITIS; DUST EXPOSURE; ASTHMA; WORKERS; PREVALENCE; LABOR